2018
DOI: 10.1109/tgcn.2018.2815645
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transmission Policies for Multi-Hop Energy Harvesting Systems

Abstract: In this paper, we consider a multi-hop energy harvesting (EH) communication system in a fullduplex mode, where arrival data and harvested energy curves in the source and the relays are modeled as general functions. This model includes the EH system with discrete arrival processes as a special case. We investigate the throughput maximization problem considering minimum utilized energy in the source and relays and find the optimal offline algorithm. We show that the optimal solution of the twohop transmission pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…where P * T S S was given in Eq. (20). The corresponding optimal time switching factor for this case becomes…”
Section: Effect Of Latency Constraintmentioning
confidence: 98%
See 1 more Smart Citation
“…where P * T S S was given in Eq. (20). The corresponding optimal time switching factor for this case becomes…”
Section: Effect Of Latency Constraintmentioning
confidence: 98%
“…[19] formulated and solved an energy efficiency optimization problem considering relays' energy harvesting constraints and average throughput constraint. [20] considered a multi-hop transmission system with EH relays, where the energy consumption of source node is minimized. [21] studied the joint transmit power minimization and EH relay selection problem to save the energy of multiple non-energy-harvesting transmitters.…”
Section: A Previous Workmentioning
confidence: 99%
“…In [17], the authors focus on the situation of hybrid energy storage, and battery imperfections situation is discussed in [18]. In [19], the authors consider a multihop EH communication system and cover all possible harvesting profiles including continuous and discrete cases. Overall the solution of offline strategies show the upper bound of optimized throughput.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, memoryless [50] and temporally correlated [36], [39] models have been considered, infinite [51] and finite [39], [49], [52] buffer capacities have been accounted for, some cases in the presence of fading communication channels [41], [31], Gaussian relay channels [46] or additive white Gaussian channels [47]- [49]. Note also that battery imperfections have been considered in [53], non ideal circuit power transmitter has been considered in [47], multi-hop duplex communications have been considered in [54], reinforcement learning techniques have been incorporated in [55] and recently in [56] it has been identified that the transmission scheduling policy does affect the EH model, a process which is naturally modelled by feedback. Significant above works involve stochastic representations of the underlying processes [9].…”
Section: Introductionmentioning
confidence: 99%